Sex Differences in Severity, Social Functioning, Adherence to Treatment, and Cognition of Adolescents with Schizophrenia. (14th September 2016) - Pérez-Garza, Rodolfo; Victoria-Figueroa, Gamaliel; Ulloa-Flores, Rosa Elena
Abstract : Background. Previous studies have reported sex differences in the clinical presentation and outcome of adult patients with schizophrenia; the aim of present study was to compare the clinical characteristics, social functioning, adherence to treatment, and cognition of adolescents with this diagnosis in a six-month followup. Methods. A total of 87 adolescents with a DSM-IV diagnosis of schizophrenia or schizophreniform disorder were evaluated with the Positive and Negative Symptoms Scale (PANSS), the Matrics Consensus Cognitive Battery (MCCB), Personal and Social Performance Scale (PSP), and the Rating of Medication Influences (ROMI). Results. Both groups showed a similar improvement in all PANSS factors and in the PSP scores during the followup. Males better adhered to treatment. Females displayed better results in the area of social cognition (F = 6.3, df = 2, 52, andp = 0.003 ) and attention/vigilance (F = 8.3, df = 2, 51, andp = 0.001 ). Conclusions. Male and female adolescents showed similar clinical presentation and functioning but a different pattern of cognitive improvement and adherence to treatment. This trial is registered with Clinicaltrials.govII3/02/0811 .‏